Nutritional composition and total collagen content of three commercially important edible jellyfish. (1st April 2016) - Khong, Nicholas M.H.; Yusoff, Fatimah Md.; Jamilah, B.; Basri, Mahiran; Maznah, I.; Chan, Kim Wei; Nishikawa, Jun
Highlights: Edible jellyfishes are rich in protein and minerals while low in fats and calories. Major amino acids present in edible jellyfishes were Gly, Pro and Glu. The main elements present within jellyfish tissues were Cl, Na, K, Mg, S and Si. Collagen was found to be the major protein in edible jellyfishes. Abstract: The study aimed to evaluate nutraceutical potential of three commercially significant edible jellyfish species ( Acromitus hardenbergi, Rhopilema hispidum and Rhopilema esculentum ). The bell and oral arms of these jellyfishes were analyzed for their proximate composition, calorific value, collagen content, amino acid profile, chemical score and elemental constituent. In general, all jellyfish possessed low calorific values (1.0–4.9 kcal/g D.W.) and negligible fat contents (0.4–1.8 g/100 g D.W.), while protein (20.0–53.9 g/100 g D.W.) and minerals (15.9–57.2 g/100 g D.W.) were found to be the richest components. Total collagen content of edible jellyfish varied from 122.64 to 693.92 mg/g D.W., accounting for approximately half its total protein content. The dominant amino acids in both bell and oral arms of all jellyfish studied includes glycine, glutamate, threonine, proline, aspartate and arginine, while the major elements were sodium, potassium, chlorine, magnesium, sulfur, zinc and silicon. Among the jellyfish, A. hardenbergi exhibited significantly higher total amino acids, chemical scores and collagen content ( p  < 0.05) compared to R. hispidum and R. esculentum . Having good protein quality and low calories, edible jellyfish is an appealing source of nutritive ingredients for the development of oral formulations, nutricosmetics and functional food.